Engineering the Fab fragment of the anti‐IgE omalizumab to prevent Fab crystallization and permit IgE‐Fc complex crystallization. Issue 3 (5th March 2020) - Mitropoulou, Alkistis N.; Ceska, Tom; Heads, James T.; Beavil, Andrew J.; Henry, Alistair J.; McDonnell, James M.; Sutton, Brian J.; Davies, Anna M.
Abstract : The omalizumab Fab was engineered to disrupt recurring crystal packing interactions in Fab crystal structures; this led to the eventual structure determination of an omalizumab‐derived Fab in complex with its target, IgE‐Fc. Abstract : Immunoglobulin E (IgE) plays a central role in the allergic response, in which cross‐linking of allergen by FcϵRI‐bound IgE triggers mast cell and basophil degranulation and the release of inflammatory mediators. The high‐affinity interaction between IgE and FcϵRI is a long‐standing target for therapeutic intervention in allergic disease. Omalizumab is a clinically approved anti‐IgE monoclonal antibody that binds to free IgE, also with high affinity, preventing its interaction with FcϵRI. All attempts to crystallize the pre‐formed complex between the omalizumab Fab and the Fc region of IgE (IgE‐Fc), to understand the structural basis for its mechanism of action, surprisingly failed. Instead, the Fab alone selectively crystallized in different crystal forms, but their structures revealed intermolecular Fab/Fab interactions that were clearly strong enough to disrupt the Fab/IgE‐Fc complexes. Some of these interactions were common to other Fab crystal structures. Mutations were therefore designed to disrupt two recurring packing interactions observed in the omalizumab Fab crystal structures without interfering with the ability of the omalizumab Fab to recognize IgE‐Fc; this led to the successful crystallization and subsequent structure determination of the Fab/IgE‐Fc complex. The mutagenesis strategy adopted to achieve this result is applicable to other intractable Fab/antigen complexes or systems in which Fabs are used as crystallization chaperones.